Kepercayaan Masyarakat terhadap Penolong Persalinan di Wilayah Halmahera Utara - Nurhidayanti, Sitti; Margawati, Ani; Kartasurya, Martha Irene (Jurnal Promosi Kesehatan Indonesia, 2018)
Background: MMR in Indonesia continues to increase, IDHS 2007 shows MMR of 228 per 100,000 in 2012 to 359 per 100,000 live births. One factor is still high maternal mortality rate due to relatively low relief by the health provider only by 55.4%. The aim of research to describe people's confidence in birth attendants in the region of North Halmahera.Method: This type of research is qualitative. Data were collected using FGD (Focus Group Discussion). Research subjects were 26 informants consisted of 7 mothers who gave birth with the help of TBAs, 2 husbands, 3 parents, 4 community leaders, 6 TBAs and 4 midwives chosen by the inclusion criteria. Analysis of data using content analysis.Results: The results showed that the informant preferring TBAs as birth attendants because informants believe TBAs are more experienced in attending births, TBAs are also considered more attention and patience in serving patients. Selection of TBAs as birth attendants associated with the services provided and the trust of society itself.Keywords: Delivery Helper, Confidence, TBAs.